How do attitudes and self-efficacy predict teachers‘ intentions to teach in inclusive classrooms? A cross-national comparison between Canada, Germany, Greece, Italy, and Switzerland. - Sahli Lozano, Caroline; Wüthrich, Sergej; Kullmann, Harry; Knickenberg, Margarita; Sharma, Umesh; Loreman, Tim; Romano, Alessandra; Avramidis, Elias; Woodcock, Stuart; Subban, Pearl

Teachers’ individual and collective efficacy in relation to their attitudes towards inclusion –Analyses from an international study comprising Canada, Germany & Switzerland. - Knickenberg, Margarita; Kullmann, Harry; Wüthrich, Sergej; Sahli Lozano, Caroline

Examining aspects of students’ current academic motivation in relation to peer interactions and social environment in the classroom using the Experience sampling method. - Knickenberg, Margarita; Zurbriggen, Carmen

Effects of peer interactions and the social environment on students’ current academic motivation in the classroom: An experience sampling study. - Knickenberg, Margarita; Zurbriggen, Carmen

Team-Teaching und Kompetenzen von Kindern im inklusiven naturwissenschaftlichen Sachunterricht. Vortrag auf der Tagung der Österreichischen Gesellschaft für Forschung und Entwicklung im Bildungswesen (ÖFEB). Thema: „Diversität diskursiv. Bildungswissenschaftliche Zugänge und pädagogische Perspektiven". - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Effekte eines universitären Kooperationstrainings auf inklusionsbezogene Selbstkonzepte von Lehramtsstudierenden. Vortrag auf der Tagung der Österreichischen Gesellschaft für Forschung und Entwicklung im Bildungswesen (ÖFEB). Thema: „Diversität diskursiv. Bildungswissenschaftliche Zugänge und pädagogische Perspektiven". - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Effekte eines universitären Lehrerkooperationstrainings auf die inklusionsbezogenen Selbstkonzepte angehender Lehrkräfte. Vortrag auf der 11. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung verstehen – Partizipation erreichen – Transfer gestalten“. - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Effects of a collaborative teacher education on pre-service teachers’ inclusion-related self-concept. Oral Paper Presentation. EARLI SIG 15 Biennial Conference 2024 ‘Special Educational Needs’. “Neurodiversity in Education: Research and Practice”. - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Effects of University Teacher Collaboration Training on the Inclusion-Related Self-Concepts of Prospective Teachers. - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Mathematikleistungen von Grundschulkindern im Zusammenhang mit dem von ihnen wahrgenommenen Feedback und ihrer Motivation im Mathematikunterricht. Vortrag auf der 11. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung verstehen – Partizipation erreichen – Transfer gestalten“ - Finke, Nils; Hellmich, Frank

An eye-tracking study on pre-service teachers' professional vision in class. Poster Presentation. EARLI SIG 15 Biennial Conference 2024 ‘Special Educational Needs’. “Neurodiversity in Education: Research and Practice”. - Görel, Gamze; Finke, Pauline; Hellmich, Frank

Effekte des Feedbacks von Lehrkräften auf die Selbstwirksamkeitsüberzeugungen und die intrinsische Motivation von Kindern im naturwissenschaftlichen Sachunterricht der Grundschule. Vortrag auf der 10. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung zwischen Unsicherheit und Evidenz“ - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Effekte eines Interventionsprogramms zur Förderung der sozialen Partizipation auf die Einstellungen von Grundschulkindern gegenüber Peers mit sonderpädagogischem Förderbedarf. Vortrag auf der 10. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung zwischen Unsicherheit und Evidenz“. - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Improving students’ attitudes towards peers with special needs: Results from an intervention study. Symposium "Chances and challenges in diverse classrooms" (Sepideh Hassani & Marwin Felix Loeper). 20th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2023. "Education as a Hope in Uncertain Times" - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Prerequisites for primary school teachers’ practices in the inclusive classroom. Symposium "Applying the Theory of Planned Behavior in Inclusive Education« (Olli-Pekka Malinen). 20th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2023. "Education as a Hope in Uncertain Times" - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Examining the Measurement Invariance and Convergent Validity of the SSIS-SELb-Student in Austria and Germany. 44th Annual Conference of the International School Psychology Association (ISPA) 2023. - Anthony, Christopher J.; Yost, M; Howe, A; Schwab, Susanne; Hassani, Sepideh; Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze

Förderung der sozialen Partizipation von Kindern im inklusiven Unterricht. Workshop auf dem 9. Paderborner Grundschultag. Thema: „Demokratie von Anfang an! Demokratie in der Grundschule erfahren, mitgestalten und reflektieren“ - Görel, Gamze; Hellmich, Frank; Löper, Marwin Felix

Professionelle Unterrichtswahrnehmung von Lehramtsstudierenden – das Projekt iDEAL. Vortrag auf der Herbsttagung 2023 der Arbeitsgruppe Empirische Sonderpädagogische Forschung (AESF) - Görel, Gamze; Finke, Pauline; Hellmich, Frank

Teachers‘ collective efficacy with regard to inclusive practices – Characterising a new scale and international results from Canada, Germany, & Switzerland - Knickenberg, Margarita; Kullmann, Harry; Wüthrich, Sergej; Sahli Lozano, Caroline; Loreman, Tim; Sharma, Umesh

Emotional-motivationales Erleben im Zusammenhang mit selbstbestimmtem Lernen im inklusiven naturwissenschaftlichen Grundschulunterricht - Knickenberg, Margarita

The composition of pre-service teacher teams and children’s competencies in inclusive education. 20th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2023. "Education as a Hope in Uncertain Times" - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Fostering students’ peer relationships through the classroom-based intervention FRIEND-SHIP. Education 3-13 - Hassani, S.; Jakob, K.; Schwab, S.; Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze (International Journal of Primary, Elementary and Early Years Education.)
Keywords: Life-span and Life-course Studies; Education

Wer kooperiert besser mit wem? – Effekte des Team-Teachings von Lehramtsstudierenden auf die Kompetenzen von Kindern im (inklusiven) naturwissenschaftlichen Sachunterricht. Vortrag auf der Sektionstagung Empirische Bildungsforschung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) und der Kommission Bildungsplanung, Bildungsorganisation und Bildungsrecht (KBBB). Thema: „Schule und Lehrkräfte. Bildung neu denken“. - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Effekte eines universitären Trainings zur Lehrerkooperation auf die inklusionsbezogenen Selbstkonzepte von Lehramtsstudierenden. Vortrag auf der Sektionstagung Empirische Bildungsforschung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) und der Kommission Bildungsplanung, Bildungsorganisation und Bildungsrecht (KBBB). Thema: „Schule und Lehrkräfte. Bildung neu denken“. - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Mathematikleistungen von Grundschulkindern im Zusammenhang mit dem von ihnen wahrgenommenen Feedback und ihren selbstbezogenen Kognitionen. Vortrag auf der Sektionstagung Empirische Bildungsforschung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) und der Kommission Bildungsplanung, Bildungsorganisation und Bildungsrecht (KBBB). Thema: „Schule und Lehrkräfte. Bildung neu denken“ - Knickenberg, Margarita; Finke, Nils; Hellmich, Frank

Kompetenzentwicklung im inklusiven Unterricht (KinU) – eine internationale Perspektive - Albers, Timm; Filipiak, Agnes; Franzen, Katja; Hellmich, Frank (Grenzen.Gänge.Zwischen.Welten. Kontroversen – Entwicklungen – Perspektiven der Inklusionsforschung)

Qualifizierung von Studierenden des Grund- und Förderschullehramts für Inklusion in Schule und Unterricht - Franzen, Katja; Albers, Timm; Hellmich, Frank (Qualifizierung für Inklusion. Grundschule)
Inklusion ist als Thema aus dem deutschen Bildungssystem nicht mehr wegzudenken und trotzdem stellt sie weiterhin eine Herausforderung auf unterschiedlichen Ebenen dar. Die Qualifizierung der pädagogischen Fachkräfte ist dabei neben der Bereitstellung adäquater Rahmenbedingungen als ein besonders wichtiges Handlungsfeld zu betrachten. Die Bände der Reihe „Qualifizierung für Inklusion“ greifen den bestehenden Forschungs- und Entwicklungsbedarf auf und geben einen Überblick über die Ergebnisse der vom BMBF im Rahmen des Programms „Qualifzierung der pädagogischen Fachkräfte für inklusive Bildung“ geförderten Forschungsprojekte. Adressiert werden damit sowohl Wissenschaftler:innen als auch mit dem Themenfeld Inklusion befasste Personen und Institutionen der Aus-, Fort- und Weiterbildung, der Bildungsadministration und der Bildungspolitik. Der zweite Band der Reihe versammelt die Vorstellung von Projekten, Ergebnissen und Materialien, die sich dem Bildungsbereich der Grundschule zuordnen lassen. Die Reihe besteht aus drei weiteren Bänden, in denen die Ergebnisse zur Qualifizierung für Inklusion im Elementarbereich (Band 1), in der Sekundarstufe (Band 3) sowie in der Berufsschule, Hochschule und Erwachsenenbildung (Band 4) vorgestellt werden.

Primary School Principals’ Views on the Required Conditions for a Successful Implementation of Inclusive Education - Görel, Gamze; Hellmich, Frank (Australasian Journal of Special and Inclusive Education)
Abstract Following the United Nations Convention on the Rights of Persons With Disabilities, questions concerning the joint education of students with and without special educational needs remain to be answered. Currently, there is a need for knowledge about the necessary conditions for a successful implementation of inclusive education. Thus, the aim of the present study is to identify conditions for the implementation of inclusion that are seen as necessary by primary school principals. Therefore, 32 primary school principals were interviewed. The results of the interview study reveal that factors like personnel, financial and material resources as well as building infrastructure in primary schools are seen as important requirements for the successful realisation of inclusive education. Apart from that, the importance of attitudes towards inclusion and sociopolitical conditions for the realisation of inclusion became apparent. Further conditions, which are mentioned from the interviewed principals’ point of view, are related to teacher training, appropriate class sizes and, for example, opportunities for exchanging information. The results of the study indicate that there are essential obstacles as perceived by primary school principals that can impede the implementation of inclusion in primary schools.
Keywords: General Engineering

Qualität der Erfahrungen aus dem inklusiven Unterricht und Selbstwirksamkeitsüberzeugungen von Grundschullehrkräften - Franzen, Katja; Moschner, Barbara; Hellmich, Frank (Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung)

Adaptiver Unterricht in der (inklusiven) Grundschule aus der Perspektive von Lehrkräften - Löper, Marwin Felix; Hellmich, Frank (Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung)

FRIEND-SHIP Intervention Program – The Handbook - Aroni, Katerina; Toulia, Anastasia; Alves, Sílvia Regina Gonçalves; Hassani, Sepideh; Heidrich, Franziska Anna; Franzen, Katja; Görel, Gamze; Löper, Marwin Felix; Aguiar, Teresa; Silveira-Maia, Mónica; Sanches-Ferreira, Maria Manuela Pires Sanches; Hellmich, Frank; et al.

Kooperatives Unterrichten von Studierenden des Lehramts an Grund- und Förderschulen als Vorbereitung auf den inklusiven naturwissenschaftlichen Sachunterricht - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne (Qualifizierung für Inklusion. Grundschule)
Inklusion ist als Thema aus dem deutschen Bildungssystem nicht mehr wegzudenken und trotzdem stellt sie weiterhin eine Herausforderung auf unterschiedlichen Ebenen dar. Die Qualifizierung der pädagogischen Fachkräfte ist dabei neben der Bereitstellung adäquater Rahmenbedingungen als ein besonders wichtiges Handlungsfeld zu betrachten. Die Bände der Reihe „Qualifizierung für Inklusion“ greifen den bestehenden Forschungs- und Entwicklungsbedarf auf und geben einen Überblick über die Ergebnisse der vom BMBF im Rahmen des Programms „Qualifzierung der pädagogischen Fachkräfte für inklusive Bildung“ geförderten Forschungsprojekte. Adressiert werden damit sowohl Wissenschaftler:innen als auch mit dem Themenfeld Inklusion befasste Personen und Institutionen der Aus-, Fort- und Weiterbildung, der Bildungsadministration und der Bildungspolitik. Der zweite Band der Reihe versammelt die Vorstellung von Projekten, Ergebnissen und Materialien, die sich dem Bildungsbereich der Grundschule zuordnen lassen. Die Reihe besteht aus drei weiteren Bänden, in denen die Ergebnisse zur Qualifizierung für Inklusion im Elementarbereich (Band 1), in der Sekundarstufe (Band 3) sowie in der Berufsschule, Hochschule und Erwachsenenbildung (Band 4) vorgestellt werden.

Effects of Teacher Feedback on Primary School Students’ Self-Efficacy Beliefs and their Interest in Science Lessons. Single Paper. ECER (European Conference on Educational Research) 2022 PLUS. “Education in a Changing World: The impact of global realities on the prospects and experiences of educational research” - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Pre-Service Teachers’ Collaborative Lesson Planning and their Self-Concepts in Inclusive Education. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Determinants for students’ attitudes towards peers with non-compliant classroom behavior in inclusive primary schools. Single Paper Presentation. AERA (American Educational Research Association) 2022. Annual Meeting Theme: „Cultivating Equitable Education Systems for the 21^st Century“, Roundtable Session: "Focus on Behavior in Special and Inclusive Education" - Löper, Marwin Felix; Lehofer, Mike; Schwab, Susanne; Hellmich, Frank

Do primary school students’ contact experiences matter for their attitudes towards peers with special needs? Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Löper, Marwin Felix; Lehofer, Mike; Schwab, Susanne; Hellmich, Frank

Primary school students’ social self-concepts, their empathy and their attitudes towards peers with social and emotional difficulties. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Löper, Marwin Felix; Hellmich, Frank

Elementary school teachers' self-efficacy beliefs concerning inclusive education. Single Paper Presentation. AERA (American Educational Research Association) 2022. Annual Meeting Theme: „Cultivating Equitable Education Systems for the 21^st Century“ - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

Primary school students’ attitudes towards peers with special educational needs – First findings of an intervention program for the promotion of students’ social participation. Symposium “Let’s be friends! The importance of social inclusion in the lives of children and adolescents” (Sepideh Hassani). ECER (European Conference on Educational Research) 2022 PLUS. “Education in a Changing World: The impact of global realities on the prospects and experiences of educational research” - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

How to improve primary school students’ social participation in the inclusive classroom? – Preliminary results from an intervention study. Oral Communication. Symposium “FRIEND-SHIP: A school-based intervention aimed at improving students’ social participation implemented in four countries” (Sílvia Alves). Porto International Conference on Research in Education 2022 (ICRE 2022) - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

The relationship between primary school students’ contact experiences and their attitudes towards peers with non-compliant behaviour. Single Paper. ECER (European Conference on Educational Research) 2022 PLUS. “Education in a Changing World: The impact of global realities on the prospects and experiences of educational research” - Löper, Marwin Felix; Lehofer, Mike; Schwab, Susanne; Hellmich, Frank

Teachers’ intentions to deal with heterogeneity in inclusive and non-inclusive primary schools. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Characteristics of good inclusive teaching from primary school teachers’ perspective. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Görel, Gamze; Franzen, Katja; Hellmich, Frank

Teachers’ experiences from teaching in (non-)inclusive primary schools and their behavioural intentions to manage heterogeneity. Oral Communication. Porto International Conference on Research in Education 2022 (ICRE 2022) - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Primary school teachers’ mastery experiences and their self-efficacy beliefs to teach in inclusive classrooms. Oral Communication. Porto International Conference on Research in Education 2022 (ICRE 2022) - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

The importance of primary school teachers’ self-efficacy beliefs and their attitudes for their everyday practices in heterogeneous classrooms. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

Elementary school teachers’ self-efficacy in inclusive education – An investigation of the associated sources. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

How to explain primary school teachers’ self-efficacy to teach in inclusive classrooms. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

The importance of parental feedback for children’s reading motivation and their reading comprehension. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Hellmich, Frank; Hoya, Fabian Karl

Effekte des Feedbacks von Lehrkräften auf die Selbstwirksamkeitsüberzeugungen und die intrinsische Motivation von Kindern im naturwissenschaftlichen Sachunterricht der Grundschule. Vortrag. 30. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE, Sektion Schulpädagogik). Thema: "Nachhaltige Bildung in der Grundschule" - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Pre-service teachers’ team-teaching practices and children’s competence development in inclusive schools. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Effects of the composition of pre-service teacher teams on primary school students’ competencies in (non-)inclusive science lessons. Paper Presentation. EARLI SIG 15 Biennial Conference 2022 `Special Educational Needs´. “A Village to Teach a Child – The Influence of Contextual Factors on Learning and Development” - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

The composition of pre-service teacher teams and primary school students’ competencies in (non-)inclusive science lessons. Oral Communication. Porto International Conference on Research in Education 2022 (ICRE 2022), Polytechnic of Porto, Centre for Research and Innovation in Education (inED) of the School of Education - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Determinants for primary school teachers’ inclusive practices in heterogenous classes. Paper Presentation. EARLI SIG 15 Biennial Conference 2022 `Special Educational Needs´. “A Village to Teach a Child – The Influence of Contextual Factors on Learning and Development” - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Quellen der Selbstwirksamkeitsüberzeugung von Grundschullehrkräften im Kontext inklusiver Erziehung und Bildung - Franzen, Katja

Erklärungsfaktoren für Handlungsintentionen von Lehrkräften an inklusiven und nicht-inklusiven Grundschulen bei der Gestaltung von adaptivem Unterricht. - Löper, Marwin Felix; Hellmich, Frank (Empirische Pädagogik)

The role of students’ experiences in attitude formation towards peers with non-compliant classroom behaviour in inclusive primary schools - Löper, Marwin Felix; Schwab, Susanne; Lehofer, Mike; Hellmich, Frank (European Journal of Special Needs Education)

Effects of pre-service teachers’ collaboration on children’s competencies and motivation in (non-)inclusive primary school science lessons - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva (International Journal of Inclusive Education)

Kompetenzentwicklung im inklusiven Unterricht (KinU) – eine internationale Perspektive - Albers, Timm; Filipiak, Agnes; Franzen, Katja; Hellmich, Frank (Grenzen. Gänge. Zwischen. Welten. Kontroversen – Entwicklungen – Perspektiven der Inklusionsforschung)

Kooperation von Lehrkräften im inklusiven Unterricht - Hoya, Fabian Karl; Hellmich, Frank (Empirische Pädagogik)

Kooperativ Forschen(d) lernen im inklusiven Sachunterricht der Primarstufe – Ein Theorie-Praxis verzahnter Ansatz zur Vorbereitung von Sachunterrichtsstudierenden auf das Praxissemester - Kirsch, Alexander; Blumberg, Eva; Hellmich, Frank; Hoya, Fabian Karl (Theorie und Praxis in der Lehrerbildung. Verhältnisbestimmungen aus der Perspektive von Fachdidaktiken)

Effects of teacher feedback on children’s self-concepts and motivation in science lessons. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

The role of teacher feedback for children’s self-concepts and motivation in primary school science lessons. Single Paper. ECER 2021 (European Conference on Educational Research). “Education and Society: expectations, prescriptions, reconciliations” - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Inklusionskompetenz von Lehramtsstudierenden im Vergleich dreier europäischer Bildungssysteme – Ergebnisse aus dem Forschungsprojekt. Vortrag. Abschlussveranstaltung der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF) - Albers, Timm; Filipiak, Agnes; Franzen, Katja; Hellmich, Frank

Inklusionskompetenz von Lehramtsstudierenden im Vergleich dreier europäischer Bildungssysteme –Schlussfolgerungen und Implikationen. Vortrag. Abschlussveranstaltung der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF) - Albers, Timm; Filipiak, Agnes; Franzen, Katja; Hellmich, Frank

Determinants for teachers’ intentions to manage heterogeneity in (non-)inclusive primary education. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

Primary school students’ contact experiences and their attitudes towards peers with disabilities. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Löper, Marwin Felix; Schwab, Susanne; Hellmich, Frank

Individual prerequisites for children’s attitudes towards peers with social-emotional disabilities. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Löper, Marwin Felix; Hellmich, Frank

The prediction of primary school teachers’ self-efficacy expectations in inclusive education. Single Paper. ECER 2021 (European Conference on Educational Research). “Education and Society: expectations, prescriptions, reconciliations” - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

Primary school principals’ views on designing inclusive schools. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Görel, Gamze; Hellmich, Frank

Die Bedeutung von Erfahrungen für die Einstellungen von Grundschulkindern gegenüber Peers mit emotional-sozialen Schwierigkeiten im inklusiven Unterricht. Vortrag auf der Tagung der Arbeitsgruppe empirische sonderpädagogische Forschung - Löper, Marwin Felix; Lehofer, Mike; Schwab, Susanne; Hellmich, Frank

Unterscheiden sich Lehrkräfte an inklusiven und nicht-inklusiven Grundschulen hinsichtlich ihrer Handlungsintentionen bei der Gestaltung adaptiven Unterrichts? Vortrag auf der Tagung der Arbeitsgruppe empirische sonderpädagogische Forschung - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Die Rolle inter- und intraindividueller Erfahrungen für die Einstellungen von Grundschulkindern gegenüber Peers mit emotional-sozialem Förderbedarf. Vortrag auf der 56. Jahrestagung der Sektion Sonderpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE). „Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung“ - Löper, Marwin Felix; Schwab, Susanne; Lehofer, Mike; Hellmich, Frank

Selbstwirksamkeitsüberzeugungen von Primarstufenlehrkräften im Kontext schulischer Inklusion – Eine Untersuchung potenzieller Prädiktoren. Vortrag auf der 56. Jahrestagung der Sektion Sonderpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE). „Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung“ - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

Handlungsintentionen bei der Gestaltung adaptiven Unterrichts – Ein Vergleich zwischen Lehrkräften an inklusiven und nicht- inklusiven Grundschulen. Vortrag auf der 56. Jahrestagung der Sektion Sonderpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE). „Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung“ - Löper, Marwin Felix; Hellmich, Frank

Bedingungen für die erfolgreiche Umsetzung von Inklusion aus Sicht von Schulleitungen an Grundschulen. Vortrag auf der 56. Jahrestagung der Sektion Sonderpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE). „Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung“ - Görel, Gamze; Hellmich, Frank

The quality of student-teacher relationship and teachers’ behaviour as predictors for children’s attitudes towards peers with learning disabilities. Single Paper. ECER 2021 (European Conference on Educational Research). “Education and Society: expectations, prescriptions, reconciliations” - Löper, Marwin Felix; Hellmich, Frank

Differentiation and individualisation as key features of inclusive teaching quality – Findings from a qualitative study with primary school teachers. Single Paper. ECER 2021 (European Conference on Educational Research). “Education and Society: expectations, prescriptions, reconciliations” - Görel, Gamze; Hellmich, Frank

The promotion of pre-service teachers’ team-teaching competencies for inclusive education. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Hellmich, Frank; Schulze, Jan Roland; Hoya, Fabian Karl

Sources of primary school teachers’ self-efficacy to teach in inclusive classrooms. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Franzen, Katja; Hellmich, Frank; Moschner, Barbara

Kooperatives Lernen von Lehramtsstudierenden im Zusammenhang mit ihrer Qualifizierung für den inklusiven naturwissenschaftlichen Sachunterricht der Grundschule – Ergebnisse aus dem Forschungsprojekt. Vortrag. Abschlussveranstaltung der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF) - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne

The impact of the composition of pre-service teacher teams on children’s competencies in (non-)inclusive primary school science lessons. Single Paper. ECER 2021 (European Conference on Educational Research). “Education and Society: expectations, prescriptions, reconciliations” - Hellmich, Frank; Schulze, Jan Roland; Blumberg, Eva; Hoya, Fabian Karl

Qualität sozialer Interaktionen von Jugendlichen mit emotionalen Problemen oder Problemen im Umgang mit Peers im Unterricht – Eine Pilotstudie mit der Experience Sampling Method - Knickenberg, Margarita; Zurbriggen, Carmen

Kooperatives Lernen von Lehramtsstudierenden im Zusammenhang mit ihrer Qualifizierung für den inklusiven naturwissenschaftlichen Sachunterricht der Grundschule – Schlussfolgerungen und Implikationen. Vortrag. Abschlussveranstaltung der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF) - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne

Qualifizierung von Studierenden des Grund- und Förderschullehramts für den inklusiven Unterricht in der Grundschule - Franzen, Katja; Görel, Gamze; Hellmich, Frank; Filipiak, Agnes; Albers, Timm (Sonderpädagogik und Bildungsforschung – Fremde Schwestern?)

School-based interventions to support student participation. A comparison of different programs. Results from the FRIEND-SHIP project - Hassani, Sepideh; Aroni, Katerina; Schwab, Susanne; Resch, Katharina; Toulia, Anastasia; Alves, Silvia; Görel, Gamze; Löper, Marwin Felix; Avramidis, Elias; Silveira- Maia, Mónica; Sanches-Ferreira, Manuela; Hellmich, Frank

Unterschiede in den Einstellungen zur Teamarbeit im inklusiven Unterricht zwischen Studierenden des Grund- und Förderschullehramts - Hoya, Fabian Karl; Schulze, Jan Roland; Hellmich, Frank (Sonderpädagogik und Bildungsforschung – Fremde Schwestern?)

Einstellungen von Kindern gegenüber Peers mit Förderbedarf: Die Rolle persönlicher Ressourcen für die soziale Partizipation. - Löper, Marwin Felix

Determinanten für die Einstellungen von Grundschulkindern gegenüber Peers mit einem sonderpädagogischen Förderbedarf in der emotionalen und sozialen Entwicklung - Löper, Marwin Felix; Hellmich, Frank (Sonderpädagogik und Bildungsforschung – Fremde Schwestern?)

Die Bedeutung von Feedback für Selbstkonzept und Motivation bei Kindern im naturwissenschaftlichen Sachunterricht der Grundschule. Vortrag auf der 8. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung gestalten – Partizipation erreichen – Digitalisierung nutzen“ - Hoya, Fabian Karl; Blumberg, Eva; Hellmich, Frank

Einstellungen von Kindern gegenüber Schülerinnen und Schülern mit einem sonderpädagogischen Förderbedarf im Zusammenhang mit dem Vorbildverhalten ihrer Eltern. Vortrag auf der 8. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung gestalten – Partizipation erreichen – Digitalisierung nutzen“ - Löper, Marwin Felix; Hellmich, Frank; Hoya, Fabian Karl

Pre-service teachers’ cooperation and children’s social participation in inclusive primary schools. Single Paper. EARLI SIG 15 Biennial Conference 2020 `Special Educational Needs´. “Learning difficulties and inclusion: Challenges (and solutions) for the future” - Hoya, Fabian Karl; Schulze, Jan Roland; Hellmich, Frank; Schwab, Susanne; Blumberg, Eva

Who cooperates better with whom? – Effects of pre-service teachers’ collaboration on children’s social participation in primary school science lessons. Oral Paper Presentation, Symposium: “Inclusive Teaching Practices – A Way to Reach Every Student?” (Katharina-Theresa Lindner). ECER 2020 (European Conference on Educational Research). “Educational Research (Re)connecting Communities” - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Schwab, Susanne; Blumberg, Eva

Persönliche Ressourcen von Grundschullehrkräften im Zusammenhang mit ihrem Umgang mit heterogenen Lerngruppen im inklusiven Unterricht. Vortrag im Rahmen des Symposiums „Individualisierung des Lernens im inklusiven Unterricht aus der Perspektive von Lehrkräften und Kindern“ (Frank Hellmich & Susanne Schwab) auf der 8. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung gestalten – Partizipation erreichen – Digitalisierung nutzen“ - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

Prädiktoren für Intentionen von Lehrkräften an inklusiven und nicht-inklusiven Schulen in Hinblick auf die Gestaltung individueller Lernprozesse. Vortrag auf der 8. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung gestalten – Partizipation erreichen – Digitalisierung nutzen“ - Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze

Predictors of primary school students’ attitudes towards peers with special educational needs in their social-emotional development. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Löper, Marwin Felix; Hellmich, Frank

Individualisierung des Lernens im inklusiven Unterricht aus der Perspektive von Lehrkräften und Kindern. Symposium auf der 8. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung gestalten – Partizipation erreichen – Digitalisierung nutzen“ - Hellmich, Frank; Schwab, Susanne

Social participation in inclusive primary education – The importance of primary school students’ contact experiences for their attitudes towards peers with special educational needs. Oral Paper Presentation, Symposium: “Social Participation of Children with Special Education Needs: Acceptance, Attitudes, Friendships and Interventions” (Sílvia Alves, Manuela Sanches-Ferreira & Mónica Silveira-Maia). ECER 2020 (European Conference on Educational Research). “Educational Research (Re)connecting Communities” - Löper, Marwin Felix; Görel, Gamze; Schwab, Susanne; Hellmich, Frank

The role of primary school teachers’ attitudes and self-efficacy beliefs for their intentions to deal with heterogeneity in (non-)inclusive education. Single Paper. ECER 2020 (European Conference on Educational Research). “Educational Research (Re)connecting Communities” - Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze

What are the requirements for a successful realisation of inclusion from primary school principals’ point of view? Single Paper. ECER 2020 (European Conference on Educational Research). “Educational Research (Re)connecting Communities” - Görel, Gamze; Hellmich, Frank